Kajian Kualitas Air Sungai Condong yang terkena Buangan Limbah Cair Industri Batik Trusmi Cirebon - Pipin Supenah; Endang Widiastuti; Rawuh Edy Priyono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2015)
The aims of this study were to assess the water quality of the River Condong and Condong River Quality Statebased on physical, chemical and biological parameters. Sampling was carried out in seven stations with 3 repetitions at intervals of one month. Water quality were analyzed descriptively by reference raw Water Quality Standard.  Determination of the stateof water quality using methods Storet. Results of laboratory tests showed that the water quality of the River Condong exceed the Water Quality Standard Group II based on Government Regulation No. 82 of 2001 and in particular textile waste quality standard TSS, DO, BOD5, COD, NH3, sulfide, Cr (VI), phenols, oils and fats, Biological parameters using makrobentos diversity index (H ') obtained a low value that is from 0 to 1.7077.  Quality state based Storet method, the value of  > -31. It can be concluded that the condition of physical, chemical and biological parameters, Condong River water showed waters not appropriate the Quality Standard for agricultural irrigation, freshwater fish breeding and infrastructure or water recreation facilities before and after the discharge of liquid waste of batik. Condong River quality state before and after the liquid waste of batik is heavily polluted.